Mediating Role of Self-Criticism in the Relationship between Fear of Negative Evaluation and Self-Compassion with Social Anxiety in Yazd Medical Students - Mehdi Shomali Ahmadabadi; Mohsen Zabihi; Ali Khodarahmi; Atefeh Barkhordari Ahmadabadi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Social anxiety is characterized by marked anxiety, cognitive and emotional dysfunction in social situations and can lead to social avoidance behavior. The purpose of this study was to investigate the mediating role of self-criticism in the relationship between the fear of negative evaluation and self-compassion with social anxiety in Yazd medical students. Methods: A correlational research study was conducted using structural equation modeling. The statistical population of the research consisted of all students of medicine, pharmacy and dentistry of Shahid Sadougi University of Medical Sciences in Yazd in the academic year of 2021-2022. The sample size of 250 people was determined; sampling was done by voluntary sampling method. Research instruments included social anxiety scale (Jarabek, 1996), fear of negative evaluation (Leary, 1983), short form of self-compassion (Rees et al., 2011) and self-criticism (Thompson and Zaroff, 2004), which were published online. Finally, the data of 227 students were analyzed by Pearson correlation and structural equation model using SPSS16 and Amos24 software. Results: The results showed that the direct effect of fear of negative evaluation and self-criticism on social anxiety was significant (P<0.001) the direct effect of self-compassion on students' social anxiety was insignificant (P<0.05) and the direct effect of fear of negative evaluation and self-compassion on self-criticism was also significant (P<0.001). Similarly, the bootstrap results showed that the effect of fear of negative evaluation and self-compassion on social anxiety through self-criticism was significant (P<0.001). Conclusion: Fear of negative evaluation significantly influences social anxiety, highlighting self-criticism's mediating role in this relationship.